Integration of mental arithmetic into the STEM education system as a means of stimulating the analytical thinking of learners - Horodetska, Natella (Педагогічна Академія: наукові записки, 2026)
The relevance of the study is determined by the increasing role of analytical thinking in the contemporary educational environment and the growing need to implement innovative approaches to the development of learners’ cognitive competencies within the expanding system of STEM education. Under conditions of digitalization and increasing complexity of interdisciplinary educational processes, particular importance is attached to identifying effective educational instruments capable of enhancing logical reasoning, concentration, cognitive flexibility, and rapid decision-making abilities. In this context, mental arithmetic is considered not only as a method of accelerated calculations, but also as a cognitive and pedagogical instrument for stimulating learners’ analytical abilities. The purpose of the article is to determine the educational potential and substantiate the effectiveness of integrating mental arithmetic into the system of STEM education for stimulating the analytical thinking of learners. The research methods are based on theoretical generalization, analysis and synthesis of scientific sources, a logical-analytical approach, and the systematization of contemporary pedagogical and methodological approaches to integrating mental arithmetic into STEM-oriented learning. As a result of the study, the pedagogical essence of mental arithmetic and its functional role in the development of analytical thinking, cognitive stability, and interdisciplinary competencies of learners have been clarified. The influence of mental arithmetic practices on the formation of logical reasoning, concentration, operational memory, and the ability to process information under dynamic educational conditions has been investigated. Methodological approaches to integrating mental arithmetic into STEM-oriented educational models, including project-oriented, adaptive, simulation-based, and collaborative learning, have been substantiated. Key scientific and practical problems associated with insufficient methodological standardization, risks of learning mechanization, cognitive overload, and unequal educational resource provision have been identified. It has been proven that the effectiveness of integrating mental arithmetic substantially increases when combined with interdisciplinary STEM practices, digital technologies, and adaptive educational models. The conclusions establish that mental arithmetic functions as an effective instrument for stimulating analytical thinking and developing learners’ cognitive flexibility within the contemporary STEM environment. Prospects for further research are associated with the empirical verification of the long-term influence of mental arithmetic on the formation of analytical competencies, as well as with the development of standardized models for its integration into digital STEM-oriented educational systems.